In dubio pro silentio – Even Loud Music Does Not Facilitate Strenuous Ergometer Exercise - Kreutz, Gunter; Schorer, Jörg; Sojke, Dominik; Neugebauer, Judith; Bullack, Antje (Frontiers in Psychology, 2018)
Background: Music listening is wide-spread in amateur sports. Ergometer exercise (spinning) is one such activity which is often performed with loud music. Aims and hypotheses: We investigated the effects of electronic music at different intensity levels on ergometer performance (physical performance, force on the pedal, pedalling frequency), perceived fatigue and heart rate in healthy adults. We assumed that higher sound intensity levels are associated with greater ergometer performance and less perceived effort, particularly for untrained individuals. Methods: Groups of high trained and low trained healthy males (N = 40; age = 25.25 years; SD = 3.89 years) were tested individually on an ergometer while electronic dance music was played at 0, 65, 75 and 85 dB. Participants assessed their music experience during the experiment. Results: Majorities of participants rated the music as not too loud (65%), motivating (77.50%), appropriate for this sports exercise (90%), and having the right tempo (67.50%). Participants noticed changes in the acoustical environment with increasing intensity levels, but no further effects on any of the physical or other subjective measures were found for neither of the groups. Therefore, the main hypothesis must be rejected. Discussion. These findings suggest that high loudness levels do not positively influence ergometer performance. The high acceptance of loud music and perceived appropriateness could be based on erroneous beliefs or stereotypes. Reasons for the widespread use of loud music in fitness sports needs further investigation. Reducing loudness during fitness exercise may not compromise physical performance or perceived effort.